PENGARUH STRATEGI PENGEMBANGAN SUMBER DAYA INSANI TERHADAP PENINGKATAN KINERJA DAN MUTU PELAYANAN PADA PT. BANK MUAMALAT INDONESIA, Tbk CABANG MEDAN - Sari Rezeki Harahap (Program Pascasarjana UIN Sumatera Utara, 2016)
This article aims to determine how much influence the direct and indirect variable among quality of the participants, instructors, materials, facilities on the performance and quality of service at PT. Bank Muamalat Indonesia, Tbk Branch Medan. The research method used is quantitative approach using path analysis with multiple linear regression model is supported by test models and statistical test using SPSS version 16. From the research conducted, the author conclude that this study on a structural 1 that is equal to 45,6% which the variable quality of the participants, instructors, materials and facilities affect service quality, while 54.4% is explained by other variables. On a structural model 2 is equal to 62.3% which the variable quality of the participants, instructors, materials and facilities affect the performance. The results of the analysis of indirect influence significance test showed indirect effect of the quality of the participants, instructors, materials and facilities to the quality of services through the variable performance significantly.